A Responsive Evaluation of Context, Process, and Outcomes of an Arabic-English Bilingual Program in an Indonesian Secondary School: التقييم الإستجابي في السياق والعمليات والنتائج لبرنامج التعليم ثنائي اللغة (العربية-الإنجليزية) في المدرسة الثانوية بإندونيسيا - Rifaldy Ali Firmansyah; Riza Nurlaila; Ahmad Farhan Rif’an Najib (UIN Raden Mas Said Surakarta, 2026)
Bilingual (Arabic-English) learning programs at the secondary school level have become a strategic approach to strengthening students’ linguistic and academic competencies; however, their implementation requires comprehensive evaluation to ensure effectiveness. This study aims to evaluate the implementation of the bilingual program at MTsN 2 Ponorogo using the responsive evaluation model, which emphasizes understanding context, process, and outcomes from the perspectives of key stakeholders. The research employed a qualitative approach, with data collected through observation, in-depth interviews, and documentation. Research participants included teachers, students, and parents, while data analysis was conducted through systematic processes of data reduction, data display, and conclusion drawing. The findings indicate that the bilingual program has been implemented in a well-planned manner and is supported by teacher preparedness, stable funding, and diverse, contextual, and interactive learning activities. In terms of outcomes, the majority of students achieved the minimum mastery criteria, demonstrated improved academic performance, and showed positive attitudes toward learning both Arabic and English. The program was also found to enhance students’ learning motivation and engagement both inside and outside the classroom. Based on these findings, this study recommends strengthening differentiated instructional strategies and conducting continuous evaluation to improve the quality and sustainability of bilingual programs at the secondary education level.